ACTUALIZATION OF PANCASILA AS A LEGAL SOURCE IN THE ESTABLISHMENT OF LEGISLATION REGULATIONS IN INDONESIA - Afifa Rangkuti; Saiful Amri (NOMOI Law Review, 2022)
The discussion of the issue of the actualization of Pancasila in the formation of laws is important because it is related to the position of Pancasila itself. For the Indonesian nation and state, Pancasila is the ideology and basis of the state. Ideology is a framework of ideals that contains the vision and mission of the state, which gives orientation to which direction the struggle and development should be directed, while the state basis is a juridical framework for the implementation of the state administration system for the survival of the nation and state. The method used in this paper is normative legal research. In the development of national law, there are still laws that are not in accordance with the values of Pancasila. This can be read, for example, from the evaluation of the National Legal Development Agency (BPHN), which in 2019 found that four of the nine laws evaluated were found to be problematic. The ten results of a study by the Pancasila Ideology Development Agency (BPIP) in 2019 also concluded that 63 of the 84 laws needed to be revised because they conflicted with Pancasila values. Based on the Law for the Establishment of Legislation, the guidelines for actualizing the values of Pancasila in the laws and regulations that are formed are contained in at least five parts.